2021
DOI: 10.48550/arxiv.2112.00884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rate-Splitting Meets Cell-Free MIMO Communications

Abstract: Multiuser multiple-input multiple-output wireless communications systems have the potential to satisfy the performance requirements of fifth-generation and future wireless networks. In this context, cell-free (CF) systems, where the antennas are distributed over the area of interest, have attracted attention because of their potential to enhance the overall efficiency and throughput performance when compared to traditional networks based on cells. However, the performance of CF systems is degraded by imperfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…We demonstrated that, compared to the trivial uniform and random allocations, the system performance is significantly improved by properly allocating the accessible heterogeneous resources of both radar and communications through ANCHOR algorithm. This study is helpful in meeting challenges of nextgeneration wireless systems where heterogeneous networks are envisaged such as different radio access technologies (RATs) and cell-free massive MIMO systems [59].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that, compared to the trivial uniform and random allocations, the system performance is significantly improved by properly allocating the accessible heterogeneous resources of both radar and communications through ANCHOR algorithm. This study is helpful in meeting challenges of nextgeneration wireless systems where heterogeneous networks are envisaged such as different radio access technologies (RATs) and cell-free massive MIMO systems [59].…”
Section: Discussionmentioning
confidence: 99%